Comparative analysis between gamma-irradiation and three chemical disinfectants using antibacterial efficacy and tensile strength of polymers. (20th January 2018) - Ahn, Dajeong; Lee, Jaewoong; Roh, Changhyun; Sul, InHwan; Kang, Chankyu
Abstract: Chemical disinfectants, widely used as antibacterial criteria, have been extensively studied for the past few decades by being divided into three levels, and γ-irradiation is also currently recognized as an outstanding antibacterial technique. However, there is no correlation between the strengths of the two methods. Antibacterial efficacy and tensile strengths of various natural and synthetic polymers inoculated with Escherichia coli (gram-negative) and Staphylococcus aureus (gram-positive) were analyzed using SEM, FT-IR, and tensile strength instruments. High and medium-level chemical disinfectants showed a similar effect to 2 kGy and 0.5 kGy of γ-irradiation doses for antibacterial analysis. In addition, the degradation of material properties through tensile strength analysis was observed only with high-level chemical disinfectants. When the correlation of high-level chemical disinfectants and γ-irradiation doses was compared through analysis of tensile strength, high-level chemical disinfectants exhibited a result equivalent to a 0.5 kGy γ-irradiation dose for synthetic polymers, while natural polymers were observed to be similar to 5 kGy for cotton and 50 kGy for wool, respectively. Graphical abstract: Image 1 Highlights: Antimicrobial efficacy and tensile strengths of various natural and synthetic polymers were analyzed. High and medium-level chemical disinfectants showed the similar effect as 2 kGy and 0.5 kGy of γ-irradiation dose for antimicrobial analysis. The degradation of material properties through tensile strength analysis was observed only at high-level chemical disinfectants. High-level chemical disinfectants had strength similar to 0.5kGy of γ-irradiation for synthetic polymers and 3kGy and 10kGy for cotton and wool.